EFEKTIVITAS METODE FAILURE MODE AND EFFECTS ANALYSIS DI BIDANG MANUFAKTUR: KAJIAN LITERATUR - Wildan, Asep; Amalia, Pujianti; Anugrah, Agung Bagja (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
To remain competitive in the era of globalization, all industries must be able to compete in the world market. The competitive global market drives all industries to become more competitive. Among all industrial sectors, manufacturing is one industry that has an important role in increasing the economy and national income. The aim of this paper is to provide insight into the literature regarding the effectiveness of FMEA in manufacturing and provide contextual knowledge as a means to improve the effectiveness of FMEA in manufacturing. The method used is a systematic literature search. The findings show that FMEA is an approach that helps companies minimize work failures and maximize production. From the results of the literature observations described, the main focus of FMEA is an approach that can be used to minimize work failures and maximize production